Developing background,service characteristics and challenges of LEO IoT - Jun SHEN; Weibin GAO; Gengxin ZHANG (Dianxin kexue)
The low earth orbit (LEO) internet of things (IoT) is an effective solution to solve the coverage inefficiency problem of terrestrial IoT in ocean,mountain and desert areas.On the basis of analyzing the developing background and situation of LEO IoT,the main application and service characteristics were given,finally the technical challenges and key technologies need to be solved for LEO IoT were discussed.